1992
DOI: 10.1113/expphysiol.1992.sp003619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of luminal flow in rabbit carotid artery on transmural fluid transport

Abstract: SUMMARYThe steady-state flow of fluid across the wall of the isolated rabbit common carotid artery has been measured in the presence and absence of flow within the lumen of the vessel. The perfusate solution contained either 10 or 40 mg ml-' albumin and transmural flux was measured by monitoring the rate of movement of fluid into a chamber enclosing the artery. Vasomotion was minimized by the inclusion of the vasodilator sodium nitrite in both the perfusate and the outer bathing solution. A relatively slow lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
2
37
1
Order By: Relevance
“…Traditionally, endothelial transport properties (L p , P d , and ) have been regarded as passive (constant) properties of the endothelium; however, it is now becoming clear that endothelial permeability coefficients depend on hemodynamic forces. Several investigators have shown that endothelial L p increases in response to an increase in fluid wall shear stress using in vitro (11,15,19,40) and in vivo (29,33,49,50) models. In the present study, a step change in the hydrostatic pressure gradient from 0 to 10 cmH 2 O induced a prominent sealing effect in BAEC monolayers (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, endothelial transport properties (L p , P d , and ) have been regarded as passive (constant) properties of the endothelium; however, it is now becoming clear that endothelial permeability coefficients depend on hemodynamic forces. Several investigators have shown that endothelial L p increases in response to an increase in fluid wall shear stress using in vitro (11,15,19,40) and in vivo (29,33,49,50) models. In the present study, a step change in the hydrostatic pressure gradient from 0 to 10 cmH 2 O induced a prominent sealing effect in BAEC monolayers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, J v/A (water flow) and Lp are often used interchangeably because ⌬P is constant; thus changes in J v/A also reflect changes in Lp. There may have been a slight excess of protein near the luminal surface because of concentration polarization driven by volume flux, but this was estimated to have a negligible oncotic effect using a 1% BSA solution (29). Integration of the bubble tracker with a fluorescent detection system allowed simultaneous flux measurements of water and fluorescent-conjugated solutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that transvascular exchange can be affected by a change in perfusion rate (14,17,19,32,33,43). A small-pore model has been proposed as a possible mechanism to account for flow-dependent transport of small solutes in cannulated vessels (32); moreover, there have been several recent studies of shearinduced increases in fluid filtration performed in vitro (3, 6, 37) and in vivo (27,40,41). The mechanism by which shear forces could increase L p appear to be dependent on nitric oxide (NO) (3,15,24).…”
mentioning
confidence: 99%